2009
DOI: 10.2478/s11756-009-0040-8
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid (ABA) treatment increases artemisinin content in Artemisia annua by enhancing the expression of genes in artemisinin biosynthetic pathway

Abstract: Artemisinin, a sesquiterpene lactone endoperoxide derived from Artemisia annua L., is the most effective antimalarial drug. In an effort to increase the artemisinin production, abscisic acid (ABA) with different concentrations (1, 10 and 100 µM) was tested by treating A. annua plants. As a result, the artemisinin content in ABA-treated plants was significantly increased. Especially, artemisinin content in plants treated by 10 µM ABA was 65% higher than that in the control plants, up to an average of 1.84% dry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 26 publications
3
68
1
Order By: Relevance
“…Although artemisinin was previously reported to be overproduced also after treatment with ABA (Jing et al 2009) and SA (Pu et al 2009), the issue of any increase in plant biomass was not addressed. The highest artemisinin contents in treated plants with ABA and SA were 1.84% DW and 1.4% DW, which was 65 and 75.8% higher than the respective controls (Jing et al 2009;Pu et al 2009). The application of salinity stress was claimed to be a simple and efficient procedure for boosting artemisinin content (2-3% DW).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although artemisinin was previously reported to be overproduced also after treatment with ABA (Jing et al 2009) and SA (Pu et al 2009), the issue of any increase in plant biomass was not addressed. The highest artemisinin contents in treated plants with ABA and SA were 1.84% DW and 1.4% DW, which was 65 and 75.8% higher than the respective controls (Jing et al 2009;Pu et al 2009). The application of salinity stress was claimed to be a simple and efficient procedure for boosting artemisinin content (2-3% DW).…”
Section: Discussionmentioning
confidence: 99%
“…Irradiation ), salinity stress (Qureshi et al 2005;Qian et al 2007), chilling stress (Feng et al 2009) and DMSO elicitation (Mannan et al 2010) have been reported to affect artemisinin production. In addition, phytohormones involved in the plant defense response [e.g., abscisic acid (Jing et al 2009) and salicylic acid (Pu et al 2009)] have also been shown to play important roles in artemisinin accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…But most of these experiments were conducted on suspension or hairy root culture of A. annua and not on large growing plants as in the present study. Published results showed that ADS expression could be up-regulated by SA and methyl jasmonate (MJ), but with no response to DMSO; CPR could be up-regulated by ABA and miconazole, but showed no response to SA and MJ; CYP could be up-regulated by low concentrations of MJ (22 M), and DMSO, but showed no response to high concentration of MJ (100 M), SA and miconazole [10,[13][14][15][16]. The responses in expression of these three genes regulated by SA in our experiments were in agreement with published reports [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…ABA, defined as a stress hormone, plays a central role in responses to biotic and abiotic stresses [21]. It was reported that ABA could stimulate the accumulation of some secondary metabolites [22,23]. Under ABA treatment, the PgSTS expression level was increased to 3.56 fold at 2 hr and rapidly decreased to minimum value at 4 hr, and then the expression increased gradually to top point 4.56 fold at 48 hr post treatments (Fig.…”
Section: Differential Expressions Of the Pgsts Under Various Abiotic mentioning
confidence: 88%